Peran Mediasi Recovery Experience dalam Hubungan antara Workplace Telepressure dan Work-Life Balance Pada Karyawan yang Tidak Memiliki Pasangan - Putri, Komang Meydiana Hutama; Endang Parahyanti (Efektor, 2022)
Today's communication technology creates a paradoxical phenomenon where the workforce experiences workplace telepressure. The workforce always feels pressure from expectations to be connected to work, not to achieve a recovery experience that can help individuals achieve work-life balance. This study examines the mediating role of the recovery experience dimensions in the relationship between workplace telepressure and work-life balance through the Hayes regression method. The results showed no significant mediating role of the recovery experience dimensions in the relationship between workplace telepressure and work-life balance. The theoretical implication of this research is that other factors such as power distance and type of activity can affect the relationship between variables in the study. The practical implication of this research is that the organization must determine the limits on when employees are allowed to work and rest.